Anterior Circulation Acute Ischemic Stroke in the Plateau of China: Risk Factors and Clinical Characteristics - Yan, Yujia; Zhang, Xiqiang; Ren, Hecheng; An, Xingwei; Fan, Wanpeng; Liang, Jingbo; Huang, Ying (Frontiers in Neurology, 2022)
Background and Purpose: Acute ischemic stroke has a high incidence in the plateau of China. It has unique characteristics compared to the plains, and the specific relationship with altitude has not yet been appreciated. This study aimed to investigate the specificity of the plateau's anterior circulation acute ischemic stroke in China. Methods: To retrospectively collect clinical data of patients with first-episode acute ischemic stroke in the anterior circulation in Tianjin and Xining city. The differences in clinical presentation, laboratory, and imaging examinations were compared. Results: Patients at high altitudes showed a significant trend toward lower age (61.0±10.2 vs. 64.8±8.1, P=0.010) and had a history of dyslipidemia, higher levels of inflammatory markers, erythrocytosis, and alcohol abuse. The main manifestations were higher diastolic blood pressure (85.5±14.0mmHg vs. 76.8±11.6mmHg, P<0.001), triglycerides [2.0(1.8) mmol/L vs. 1.3(0.9) mmol/L, P<0.001], CRP [4.7(4.4) mg/L vs. 2.1(1.9) mg/L, P<0.001], homocysteine levels [14.5(11.7) µmol/L vs. 11.2(5.2) µmol/L, P<0.001]; larger infarct volume [3.5(4.8) cm3 vs. 9.0(6.9) cm3, P<0.001] and worse prognosis. Patients at high altitudes had higher atherosclerotic indexes in cIMT and plaque than those in plains. Conclusions: The natural habituation and genetic adaptation of people to the particular geo-climatic environment of the plateau have resulted in significant differences in disease characteristics. Patients with the anterior circulation acute ischemic stroke in the plateau show more unfavorable clinical manifestations and prognosis. This study provides a preliminary interpretation of the effects of altitude and suggests developing preventive and therapeutic protocol measures that are more appropriate for the plateau of China.